Reform and Growth in Latin America: All Pain, No Gain? - Eduardo Fernández-Arias; Peter Montiel (Inter-American Development Bank, Office of the Chief Economist, 1997)
This paper addresses the adequacy of post-reform growth in Latin America in the 1990s on the basis of international comparison and other relevant standards. It analytically explores and empirically tests a number of hypotheses to explain the perceived dissatisfaction with growth performance.
Keywords: 330